An abstract machine for the execution of DeLP programs - Stankevicius, Alejandro G. (2004)
Defeasible Logic Programming (DeLP) is a knowledge representation and reasoning formalism that by combining Logic Programming with Defeasible Argumentation is able to represent incomplete and potentially contradictory information. Within the field of Logic Programming, most of the implementations of Prolog and its variants are based on an abstract machine defined by D. Warren (nowadays known as WAM, standing for Warren’s Abstract Machine), that sits between the program and the actual hardware executing it. This separation of concerns allows the developer to focus mainly on the aspects related to the language being implemented, and not on the distinctive characteristics of the available hardware. In this paper we summarize how an abstract machine can also help in the context of DeLP, exploring the points of contact between WAM and a particular abstract machine defined for this theory called JAM.